Formation of PCDTBT:PC71BM p–n junction composite nanotubes via a templating method. Issue 124 (30th November 2015) - Bakar, N. A.; Supangat, A.; Sulaiman, K.
Abstract : The use of a templating method to synthesize a p–n junction composite of PCDTBT:PC71 BM is reported in this study. Abstract : The use of a templating method to synthesize a p–n junction composite of poly[ N -90-hepta-decanyl-2, 7-carbazole- alt -5, 5-(40, 70-di-2-thie-nyl 20, 10, 30 benzothiadiazole)] (PCDTBT):[6, 6]-phenyl C71 -butyric acid methyl ester (PC71 BM) is reported in this study. These materials have been studied due to their potential applications in organic electronic-based devices. Intimate contact between these materials can be realised via a facile fabrication using the template-assisted method. The formation of a p–n junction composite was elaborated in which its properties were compared to its bulk heterojunction counterpart. PCDTBT nanorods, nanotubes and nanoflowers were first produced followed by infiltration of PC71 BM. A remarkable pattern at the first peak (carbazole) could be seen from the UV-vis spectra of the PCDTBT:PC71 BM p–n junction composite nanotubes at a higher concentration of 15 mg ml −1 . However, the reverse condition was seen for its lower concentration of 5 mg ml −1, which showed improvement in the second peak (DTBT) in the UV-vis spectra. The first peak of the 10 mg ml −1 solution concentration shows a wider peak compared to the 5 and 15 mg ml −1 concentrations with its second peak having fallen between these two concentrations. Unlike the PCDTBT:PC71 BM bulk-heterojunction, which showed better quenching, PCDTBT:PC71 BM composite nanotubes have shown a significant red-shift in their photoluminescence (PL) spectra. Despite having a significant red-shift, the PCDTBT:PC71 BM junction composites displayed poor quenching properties.